تجريف الرحم الاستقصائي - سلمان صفاء; صالح حسن; معلا زينب (Latakia University Journal -Medical Sciences Series, 2019)
أجري البحث في مشفى الأسد الجامعي باللاذقية قسم التوليد وأمراض النساء في الفترة بين 1/11/2002 و1/6/2004 وقد بلغ عدد مريضات الدراسة 162 حالة تجريف رحم استقصائي وشكلت 7.7% من مجموع المريضات اللواتي قبلن في قسم الأمراض النسائية في هذه الفترة و11.4% من مجموع العمليات الجراحية النسائية بمختلف أنواعها وقد احتلت فئة العمر 40-49سنة الذروة في نسبة إجراء التجريف الاستقصائي وبلغت59.3%. وقد توزعت استطبابات التجريف الاستقصائي بالشكل التالي: نزف رحمي شاذ 53.7%. اضطرابات طمثية 32.7%. نزف بعد الجماع4.9%. بوليب عنق رحم 4.9%. استطبابات أخرى 3.8%. وكانت نتائج التشريح المرضي للتجاريف الاستقصائية كما يلي: بطانة إفرازية 29.6%. فرط تصنع بطانة الرحم 25.9%. بطانة تكاثرية 13.6%. بوليب عنق رحم 8.6%. بطانة التهابية 7.4%. بطانة ضمورية 3.7%. بوليب باطن الرحم 3.7%. آفات خبيثة 2.4%. انسلاخ غير منتظم للبطانة الرحمية 3.7%. علقات دموية وألياف عضلية ملساء 1.2%. وكانت الأختلاطات قليلة ونسبتها 1.8%. وكان أهم اختلاط للتجريف الاستقصائي إنتان باطن الرحم بنسبة 1.2 % تلاه رض عنق الرحم بنسبة 0.6% ولم تحدث أية حالة انثقاب رحم. The research was conducted in the department of obstetrics and gynecology in AL ASSAD University Hospital in Lattakia between 1/11/2002 – 1/6/2004 and included 162 patients, D&C have been made to all these patients. These patients are about 7.7% of all patients were accepted in the department of Gynecology. And this number forms 11.4% of all surgical Gynecological operations. 59.3% of patients who have had D&C were 40-49 year old. The indications of D&C were : Abnormal uterine bleeding 53.7%. menstrual disturbances 32.7%. Post coital bleeding 4.9%. Cervical polyp 4.9%. Other indications 3.8%. And the pathological results of D&C were: Secretory endometrium 29.6%. Hyperplastic endometrium 25.9%. Proliferative endometrium 13.6%. Cervical polyp 8.6%. Inflammatory endometrium 7.4%. Atrophic endometrium 3.7%. Endometrial polyp 3.7%. Malignants lesions 2.4%. Irregular shedding of the endometrium 3.7%. Smooth muscle fibers and clots 1.2%. The complications were 1.8% and the most important complication was endometritis 1.2% and cervical trauma 0.6%. there was no uterine perforation.